Trends in competitive balance: Is there evidence for growing imbalance in professional sport leagues? - Arne Feddersen; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2005)
The concept of competitive balance is a central aspect in the literature of sports economics. A popular argumentation of sport functionaries is that dominance of one or a few teams could lead to unequal incomes for the clubs, restrictions in the clubs' ability to improve sporting performance and ultimately to a loss of attractiveness and loss of income for the league. Following this line of reasoning and alleging a negative trend in competitive sports functionaries often try to implement regulations in team sport leagues. The aim of this paper is to analyze for eight different leagues if there is such a trend existing. For an empirical test for trends in competitive balance of four European soccer leagues (ENG, ESP, GER, ITA) and four US Major Leagues (MLB, NBA, NFL, NHL), OLS regressions with a constant were carried out. For the entire observation period from 1969/70 to 2003/2004, of 48 trends ascertained, only 12 could be observed as being significantly positive (i.e. growing imbalance) with 19 significantly negative (i.e. growing balance). The remaining 17 trends were insignificantly different from zero.
Keywords: L83; C22; 330; Competitive Balance; Sports Economics; Team Sport Leagues; Trend